Ovine enzootic calcinosis by ingestion of Nierembergia veitchii - Barros, Claudio S. L.; Rissi, Daniel R. (Brazilian Journal of Veterinary Pathology, 2024)
A chronic wasting disease occurred in sheep from a flock in southern Brazil (29° 32’ 16” S 53° 51’ 18” O) from October 2003 to January 2004. Of a total population at risk of 460 sheep, 43 were affected, 29 died spontaneously, and 10 were euthanized. Clinical signs included weight loss, cachexia, rigid walking, retracted abdomen, and kyphosis. In some cases, terminal pulmonary edema led to oozing of abundant white foam from the nasal and oral cavities. Nierembergia veitchii (Fig. 1) was present in the pastures where the affected sheep were held.